Reproducibility of histamine challenge tests in asthmatic children. - Hariparsad, D (1983)
The measurement of bronchial reactivity by histamine challenge testing is of increasing clinical importance in paediatrics. By means of a simple tidal breathing technique for the measurement of histamine sensitivity (expressed as PC20--the concentration of histamine which produces a 20% fall in peak flow rate) in childhood asthma, the reproducibility of pairs of tests was estimated over one hour and 24-hour intervals in 22 children. Under carefully controlled conditions the 95% confidence limits of PC20 were 0.8-1.25 X baseline PC20 after one hour and 0.36-2.8 X baseline PC20 after 24 hours.